Improving the diffraction efficiency of structures in direct laser writing using obliquely incident beams: modeling and experiment - V.P. Kiryanov; N.A. Gurin (Компьютерная оптика, 2023)
A brief review of methods for increasing the diffraction efficiency of optical elements synthesized by direct laser writing is done. It is noted that the previously proposed methods for recording the topology of similar elements using volumetric or surface contour masks do not provide an ultimate solution to a problem of increasing the diffraction efficiency. The performed model and physical experiments on the fabrication of structures of surface-relief phase optical elements by recording zone profiles using oblique laser beams show the fundamental possibility of forming steep side walls of the reverse zone slopes and the feasibility of developing this technology based on laser image generators.